2017
DOI: 10.1080/09602011.2017.1344132
|View full text |Cite
|
Sign up to set email alerts
|

Description of a multifaceted intervention programme for fatigue after acquired brain injury: a pilot study

Abstract: The purpose of this pilot study was to describe and explore a group-based multifaceted intervention for patients with fatigue after acquired brain injury (ABI). We hypothesised that post-intervention changes would result in reduced fatigue, in addition to improved emotional health, sleep and attentional control. Eight subjects with traumatic brain injury (n = 3) and cerebrovascular insults (n = 5) were included. Inclusion was based upon the presence of fatigue complaints. The participants received 36 hours of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 98 publications
0
15
0
Order By: Relevance
“…Indeed Skogestad et al reported 24 distinct self-report measures of PSF across 78 reviewed studies including three of the four measures discussed in this review the FSS, the MFS, and the CIS-f subscale. Given the plethora of measures available, we support the statement by Stubberud et al (2019) that researchers and clinicians may find it useful to use more than one measure to gain a full understanding of PSF in their clients. Skogestad et al were able to categorize the items in the measures they reviewed into four dimensions: quality of fatigue (e.g., weakness), severity of fatigue (e.g., tired every day), interference (e.g., prevents sustained function), and coping/management (e.g., pace activity).…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…Indeed Skogestad et al reported 24 distinct self-report measures of PSF across 78 reviewed studies including three of the four measures discussed in this review the FSS, the MFS, and the CIS-f subscale. Given the plethora of measures available, we support the statement by Stubberud et al (2019) that researchers and clinicians may find it useful to use more than one measure to gain a full understanding of PSF in their clients. Skogestad et al were able to categorize the items in the measures they reviewed into four dimensions: quality of fatigue (e.g., weakness), severity of fatigue (e.g., tired every day), interference (e.g., prevents sustained function), and coping/management (e.g., pace activity).…”
Section: Discussionmentioning
confidence: 54%
“…In relation to participants, the vast majority had sustained their stroke more than 1 year prior to receiving an intervention for PSF and the majority lived in the community, either receiving the intervention as a community program or as an outpatient. The participant demographics across studies reflect those of the general stroke population with exceptions in three studies (Johansson, Bjuhr, Karlsson, et al, 2015; Johansson et al, 2012; Stubberud et al, 2019) in which the average age was younger, and the samples comprised of fewer males compared with a typical PSF population (Cumming et al, 2016). This suggests that the benefits found in the studies reviewed may extend to a broad population in relation to age and sex.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations